Effects of Circuit Resistance Training and Aerobic Circuit Resistance Training on Performance Related Fitness Components of Female Volleyball Players - Geeta M.Vala; Dr. Bharat V. Chaudhari (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The study was designed to investigate “The effects of circuit resistance training and aerobic circuit resistance training on performance related fitness components of female Volleyball players” for this forty five Volleyball players were selected randomly from ranged from 15 to 17 years. they were divided into two equal Group -1 underwent circuit resistance training group. in a week five days the Group - 2 underwent Aerobic circuit resistance training.Group-3 is acted as control that did participatein any special training programme apart from their regular activities as per their regular activities as per their curriculum. Speed was chosen as a criterion variable. it assessed by 50 meters run test before and after the training period of twelve weeks. The analysis of covariance was used to determine of any significant difference was present among the three groups of the dependent variables. The study revealed that the selected criterion variable were significantly improved due to the influence of circuit resistance training and aerobic circuit resistance training on speed of femaleVolleyball players.